1995
DOI: 10.1111/j.1467-6494.1995.tb00506.x
|View full text |Cite
|
Sign up to set email alerts
|

The Personal Script as a Unit of Analysis for the Study of Personality

Abstract: This article presents the construct of a "personal script" as an itnportant variable for the study of personality. Personal scripts are construals that individuals form to understand and deal with personally significant experiences of living. A nutnber of differences are outlined between the personal script constmct and the field's tnore predotninant trait construct. It is argued that the personal script construct can provide new perspectives on questions which have been addressed previously by the trait const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 40 publications
0
37
0
1
Order By: Relevance
“…Procedural knowledge means that we all know what to do in a restaurant: enter, wait to be seated, get the menu, order, eat, get the bill, pay, and exit (Cornish, 1994). Scripts are mostly unconscious, socially learnt, extremely resistant to change, and influence how one attends to, organizes, and recalls information (Baldwin, 1992; Beauregard, Proulx, Rossmo, Leclerc, & Allaire, 2009;Demorest, 1995;Zadney & Gerard, 1974). Memory has been shown to be particularly susceptible to the influence of scripts (Bellezza & Bower, 1981;Bower, Black, & Turner, 1979;Gibbs & Tenney, 1980;Graesser, Woll, Kowalski, & Smith, 1980).…”
Section: Scripts: General Conceptsmentioning
confidence: 97%
“…Procedural knowledge means that we all know what to do in a restaurant: enter, wait to be seated, get the menu, order, eat, get the bill, pay, and exit (Cornish, 1994). Scripts are mostly unconscious, socially learnt, extremely resistant to change, and influence how one attends to, organizes, and recalls information (Baldwin, 1992; Beauregard, Proulx, Rossmo, Leclerc, & Allaire, 2009;Demorest, 1995;Zadney & Gerard, 1974). Memory has been shown to be particularly susceptible to the influence of scripts (Bellezza & Bower, 1981;Bower, Black, & Turner, 1979;Gibbs & Tenney, 1980;Graesser, Woll, Kowalski, & Smith, 1980).…”
Section: Scripts: General Conceptsmentioning
confidence: 97%
“…For example, McAdams et al (2001) studied contamination scripts (where positive affect is followed by a negative affective outcome) and redemption scripts (where negative affect is followed by a positive affective outcome). More generally, several different investigators have provided empirical support for both the concept of scripts and the process of psychological magnification (Carlson & Carlson, 1984;Demorest, 1995;Demorest & Alexander, 1992;McAdams, Reynolds, Lewis, Patten, & Bowman, 2001;Thorne, 1995), while clinical case studies have also demonstrated the utility of the theory (Carlson, 1981;Magai, 1996 . According to script theory, SDMs are memorial representations that ground narrative sequences of actions, affects, and outcomes in specific autobiographical memories.…”
Section: Self-defining Memories In the Sms Modelmentioning
confidence: 99%
“…O'Connor, Cermak, & Seidman, 1995). The Conceptual Self is then depicted as a separate system in Figure 2 and consists of non-temporally specified conceptual self-structures, such as personal scripts (Demorest, 1995;Thorne, 1995;J.A. Singer & Salovey, 1993;Tomkins, 1979), possible selves (Markus & Nurius, 1986), self-with-other units (Ogilvie & Rose, 1995), conceptual aspects of internal working models (Bowlby, 1969(Bowlby, /1982(Bowlby, , 1973(Bowlby, , 1980, relational schemas (Baldwin, 1992), self-guides (Strauman, 1990;Strauman & Higgins, 1987), attitudes, values and beliefs.…”
Section: The Conceptual Selfmentioning
confidence: 99%
“…Scripts operate unconsciously, are highly resistant to change (Demorest, 1995), and influence cognitive processes including attention, organization, interpretation, and recall of information (Baldwin, 1992;Zadney & Gerard, 1974).…”
mentioning
confidence: 99%